2000
DOI: 10.1080/03079450050118412
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of fimbriae and flagella ofSalmonella enteritidisto colonization and invasion of chicks

Abstract: Isogenic mutants of Salmonella enteritidis defective for the elaboration of fimbrial types SEF14, SEF17, SEF21 and flagella were used to study the contribution these organelles made to colonization, invasion and lateral transfer in young chicks. The caecum, liver and spleen were colonized within 24 h following oral inoculation of 1-day-old chicks with 10(5) wild-type S. enteritidis strain LA5. However, for some mutants, the numbers of organisms recovered from internal organs was reduced significantly, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 54 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…However, it is possible that differences in intestinal invasiveness of Salmonella serotypes only lead to differences in the time needed to establish the generalized infection and not to differences in severity of infection. A report by Dibb-Fuller & Woodward (2000) could be taken as support for this because they showed that impairment of flagella and fimbriae function, and thereby a possible impairment of invasion in mutants of S. Enteritidis only leads to a delay in the establishment of the generalized infection measured as the time of colonization of internal organs. The particular ability of S. Enteritidis PT4 to infect the egg may not be related to invasion, but rather to unknown virulence determinants unique to this serotype (Keller et al, 1997).…”
Section: Discussionmentioning
confidence: 95%
“…However, it is possible that differences in intestinal invasiveness of Salmonella serotypes only lead to differences in the time needed to establish the generalized infection and not to differences in severity of infection. A report by Dibb-Fuller & Woodward (2000) could be taken as support for this because they showed that impairment of flagella and fimbriae function, and thereby a possible impairment of invasion in mutants of S. Enteritidis only leads to a delay in the establishment of the generalized infection measured as the time of colonization of internal organs. The particular ability of S. Enteritidis PT4 to infect the egg may not be related to invasion, but rather to unknown virulence determinants unique to this serotype (Keller et al, 1997).…”
Section: Discussionmentioning
confidence: 95%
“…In S. Typhimurium, genes implicated in colonization include the type III secretion system genes of SPI-1 and SPI-2 (71), lpf and pef (78), and lipopolysaccharide biosynthesis genes (112). In S. Enteritidis, genes implicated in colonization include the type VI secretion system genes of SPI-19 (9) and the type III secretion system genes of SPI-2 (122), hilA (10), and the genes encoding fimbrial types SEF17 and SEF21 (34). However, given that the colonization mechanisms differ between hosts, between serovars, and even within an individual serovar, there is still much to understand related to colonization mechanisms employed by S. Heidelberg and S. Kentucky within the avian host.…”
Section: Genetic Factors Contributing To the Emergence Of Salmonella mentioning
confidence: 99%
“…Infection by Salmonella Enteritidis is initiated by the attachment and colonization of the gut mucosa, which seems to be an essential stage in the pathogenesis of salmonellosis. Increasing evidence suggests that bacterial fimbriae play an important role in these processes (De Buck et al, 2003;Dibb-Fuller et al, 1999;Dibb-Fuller & Woodward, 2000;Ewen et al, 1997;Naughton et al, 2001), although their exact role in the pathogenesis of Salmonella is still controversial (Rajashekara et al, 2000;.…”
Section: Introductionmentioning
confidence: 99%